(untitled) (Journal of Dhaka National Medical College & Hospital, 2021)
Objective: Aim of this study to describe factors associated with sepsis in diarrheal adults and to see clinical and laboratory profile of those patients as well as to see outcome of sepsis in diarrheal patients. Methodology: This was observational prospective study done among 200 diarrheal patients admitted in an urban hospital from June 2019 to February 2020. Results: Among 200 adult diarrheal patients, 67.5% were male, 32.5% were female and 44.44% male and 53.58% female subsequently developed features of the sepsis. Hyponatremia (75%) and Hypokalemia (65%) was the commonly observed electrolytic imbalance and 55% of respondent developed AKI. Prior antibiotic use, systematic steroid intake and presence of co-morbidity were most significant risk factors for development of sepsis. Conclusion: Diarrheal adults who had history of steroid intake for long, prior antibiotic use and who had multiple co-morbidities are in high risk to develop sepsis. J. Dhaka National Med. Coll. Hos. 2021; 27 (02): 11-14